Zooplankton-mediated nutrient limitation patterns in marine phytoplankton: an experimental approach with natural communities - Trommer, Gabriele; Pondaven, Philippe; Siccha, Michael; Stibor, Herwig (Marine Ecology Progress Series, 2012)
International audience Zooplankton nutrient recycling has been shown to substantially affect nutrient availability for phytoplankton. However, investigations are required to determine whether zooplankton also influence nutrient limitation in marine phytoplankton communities, and whether grazing by different zooplankton groups results in different patterns of phytoplankton nutrient limitation. We performed laboratory experiments under different nutrient supply conditions on a variety of phytoplankton communities with natural densities of copepods and rotifers, and tested phytoplankton nutrient limitation in bioassays for nitrogen, phosphorus, and the combination of the two. After 5 d incubation with zooplankton, we observed a significant increase in phytoplankton biomass in the zooplankton treatments. We relate this largely to nutrient recycling effects, which are amplified through possible trophic cascade effects. In copepod treatments, the highest phytoplankton biomass was reached under Redfield and nitrogen excess nutrient supply conditions, while the highest biomass in rotifer treatments was registered under phosphorus excess conditions. In most cases, nutrient limitation assays revealed a co-limitation of phytoplankton by nitrogen and phosphorus. With increasing nitrogen supply, we observed an increase in phosphorus limitation in the copepod treatments and a decrease in nitrogen limitation in the rotifer treatments. The phytoplankton community was driven into phosphorus limitation under nitrogen excess conditions in copepod treatments. Our results indicate that natural densities of zooplankton are able to promote nitrogen and phosphorus co-limitation in phytoplankton communities.